DIAGNOSING THE READINES OF TECHNICAL UNIVERSITY STUDENTS FOR RESEARCH ACTIVITIES - M. A. Fedorova; A. M. Zavyalov (Образование и наука)
The paper is devoted to the technique designed for diagnosing the technical university student’s readiness for research activities that is closely related to the research competence structure. Based on the survey results and literature analysis, the authors considered ten primary components of the readiness in question, and analyzed each component along with the corresponding weight value, mean value, and probability density. Consequently, the high level of academic knowledge and motivation for research activity were singled out as the priority components. The paper describes the linear mathematical model, developed for diagnosing student’s readiness for research activities, and presents the minimum, maximum and threshold values of diagnostic assessments, and the relating indicators. The given model can be used as the basic one for developing a test software product for students and research supervisors diagnosing the readiness for research activity